2005
DOI: 10.1080/08035250410023629
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure in the neonate: Three non-invasive oscillometric pressure monitors compared with invasively measured blood pressure

Abstract: Children's psychiatric problems are manifested at school mostly as behavioural problems. A two-parent family and being the oldest in the sibling series seem to be protective factors. Very large family size, if not connected to social disadvantages, does not seem to be a risk factor for children's behaviour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
3

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 28 publications
3
58
3
Order By: Relevance
“…A previous study of term and preterm infants showed that the measurement discrepancy between NBP and arterial measurements may be related to infant size, with smaller infants having a larger measurement discrepancy. 9 We found that a lower birth weight was associated with a larger differential in systolic NBP and UAC measurements, but we did not find this association in mean or diastolic blood pressure measurements. Systolic blood pressure may be more strongly influenced by birth weight, or the lack of association between mean and diastolic differentials and low birth weight may be caused by the fact that our cohort was limited to small infants, in which NBP measurements were inaccurate across the entire birth weight range.…”
Section: Blood Pressure Measurements In Elbw Infantscontrasting
confidence: 86%
See 1 more Smart Citation
“…A previous study of term and preterm infants showed that the measurement discrepancy between NBP and arterial measurements may be related to infant size, with smaller infants having a larger measurement discrepancy. 9 We found that a lower birth weight was associated with a larger differential in systolic NBP and UAC measurements, but we did not find this association in mean or diastolic blood pressure measurements. Systolic blood pressure may be more strongly influenced by birth weight, or the lack of association between mean and diastolic differentials and low birth weight may be caused by the fact that our cohort was limited to small infants, in which NBP measurements were inaccurate across the entire birth weight range.…”
Section: Blood Pressure Measurements In Elbw Infantscontrasting
confidence: 86%
“…[2][3][4] However, it is unclear how NBP and arterial blood pressure measurements compare in preterm infants. [5][6][7][8][9][10][11][12] Data on the correlation between NBP and arterial measurements in extremely low-birth-weight (ELBW) infants are particularly lacking. One small study, evaluating systolic NBP and arterial blood pressure measurements, showed discrepant NBP and arterial measurements in infants who weighed <750 g. 13 The aim of this study was to compare measurements of systolic, mean and diastolic blood pressures obtained using noninvasive means with measurements procured from a central arterial catheter in newborn ELBW infants.…”
Section: Introductionmentioning
confidence: 99%
“…This study showed that the oscillometric device tended to overestimate BP in infants with low BP [20]. Other studies carried out in mixed preterm and term infant population demonstrated both over-and underestimation of the arterial mean BP, with overestimation the more common phenomenon [21][22][23].…”
Section: Introductionsupporting
confidence: 48%
“…A number of studies have compared the automated oscillometric method with direct intra-arterial blood pressure monitoring in neonates and have found a high correlation between mean blood pressure measurements by these two methods, with correlation coefficients ranging from 0.85 to 0.97 (21). In order to minimize errors in noninvasive MABP measurement it is suggested to choose an appropriate size cuff, to obtain blood pressure during a quiet or sleeping state, and to obtain an average of three measurements (21,22). Our refractory hypotensive patients presented low MABP throughout the study period despite the use of volume expansion and vasopressor drugs.…”
Section: Resultsmentioning
confidence: 99%